Serum zinc levels and in vivo beta-amyloid deposition in the human brain - Jee Wook Kim; Min Soo Byun; Dahyun Yi; Jun Ho Lee; Min Jung Kim; Gijung Jung; Jun-Young Lee; Koung Mi Kang; Chul-Ho Sohn; Yun-Sang Lee; Yu Kyeong Kim; Dong Young Lee; et al. (Alzheimer’s Research & Therapy, 2021)
Abstract Background Despite the known associations between zinc levels and Alzheimer’s disease (AD) dementia and related cognitive impairment, the underlying neuropathological links remain poorly understood. We tested the hypothesis that serum zinc level is associated with cerebral beta-amyloid protein (Aβ) deposition. Additionally, we explored associations between serum zinc levels and other AD pathologies [i.e., tau deposition and AD-signature cerebral glucose metabolism (AD-CM)] and white matter hyperintensities (WMHs), which are measures of cerebrovascular injury. Methods A total of 241 cognitively normal older adults between 55 and 90 years of age were enrolled. All the participants underwent comprehensive clinical assessments, serum zinc level measurement, and multimodal brain imaging, including Pittsburgh compound B-positron emission tomography (PET), AV-1451 PET, fluorodeoxyglucose (FDG)-PET, and magnetic resonance imaging. Zinc levels were stratified into three categories: < 80 μg/dL (low), 80 to 90 μg/dL (medium), and > 90 μg/dL (high). Results A low serum zinc level was significantly associated with increased Aβ retention. In addition, apolipoprotein E ε4 allele (APOE4) status moderated the association: the relationship between low zinc level and Aβ retention was significant only in APOE4 carriers. Although a low zinc level appeared to reduce AD-CM, the relationship became insignificant on sensitivity analysis including only individuals with no nutritional deficiency. The serum zinc level was associated with neither tau deposition nor the WMH volume. Conclusions Our findings suggest that decreased serum zinc levels are associated with elevation of brain amyloid deposition. In terms of AD prevention, more attention needs to be paid to the role of zinc.